Urethral and bladder dosimetry of total and focal salvage Iodine-125 prostate brachytherapy: Late toxicity and dose constraints. Issue 2 (November 2015) - Peters, Max; van der Voort van Zyp, Jochem; Hoekstra, Carel; Westendorp, Hendrik; van de Pol, Sandrine; Moerland, Marinus; Maenhout, Metha; Kattevilder, Rob; van Vulpen, Marco
Abstract: Introduction: Salvage Iodine-125 brachytherapy (I-125-BT) constitutes a curative treatment approach for patients with organ-confined recurrent prostate cancer after primary radiotherapy. Currently, focal salvage (FS) instead of whole-gland or total salvage (TS) is being investigated, to reduce severe toxicity associated with cumulative radiation dose. Differences in urethral and bladder dosimetry and constraints to reduce late (>90 days) genitourinary (GU) toxicity are presented here. Materials and methods: Dosimetry on intraoperative ultrasound (US) of 20 FS and 28 TS patients was compared. The prostate, bladder, urethra and bulbomembranous (BM) urethra were delineated. Toxicity was assessed using the CTCAE version 4.0. Dose constraints to reduce toxicity in TS patients were evaluated with receiver operating characteristic (ROC) analysis. Results: FS I-125 BT significantly reduces bladder and urethral dose compared to TS. Grade 3 GU toxicity occurred once in the FS group. For TS patients late severe (⩾grade 3) GU toxicity was frequent (38% in the total 61 patients and 56% in the 27 analyzed patients). TS patients with ⩾grade 3 GU toxicity showed higher bladder D2 cc than TS patients without toxicity (median 43 Gy) ( p = 0.02). The urethral V100 was significantly higher in TS patients with several toxicity profiles: ⩾grade 3 urethral strictures, ⩾grade 2 urinary retention and multiple ⩾grade 2 GU toxicity events. Dose to the BM urethra did not show a relation with stricture formation. ROC-analysis indicated a bladder D2 cc <70 Gy to prevent ⩾grade 3 GU toxicity (AUC 0.76, 95%CI: 0.56–0.96, p = 0.02). A urethral V100 <0.40 cc (AUC from 0.73–0.91, p = 0.003–0.05) could prevent other late GU toxicity. Conclusion: FS I-125 BT reduces urethral and bladder dose significantly compared to TS. With TS, there is an increased risk of cumulative dose and severe GU toxicity. Based on these findings, bladder D2 cc should be below 70 Gy and urethral V100 below 0.40 cc.